The Relationship Between Husband's Emotional Support and Mothers' Confidence in Exclusive Breastfeeding in the Work Area of the Central City Community Health Center - Ainun Yus’iranna Ihram; Ridha Hafid; Siti Hajar Salawali (Universitas Muhammadiyah Palu, 2026)
Background: Maternal self-confidence is one of the key determinants of successful exclusive breastfeeding. One of the factors that may influence maternal confidence is the emotional support provided by husbands during the breastfeeding period. Emotional support, including attention, empathy, affection, and encouragement, can improve mothers' psychological well-being and strengthen their confidence in exclusively breastfeeding their infants. Objective: This study aimed to analyze the relationship between husbands' emotional support and maternal self-confidence in exclusive breastfeeding at the Kota Tengah Community Health Center. Methods: This quantitative study employed a cross-sectional design. The study population consisted of 103 breastfeeding mothers, with 82 respondents selected through purposive sampling. Data were collected using questionnaires measuring husbands' emotional support and maternal self-confidence in exclusive breastfeeding. Data were analyzed using descriptive statistics and Pearson Product-Moment correlation with a significance level of 0.05. Results: Most respondents reported receiving high emotional support from their husbands (97.6%) and demonstrated high self-confidence in exclusive breastfeeding (76.8%). Bivariate analysis revealed a significant relationship between husbands' emotional support and maternal self-confidence in exclusive breastfeeding (p = 0.018; r = 0.262). The correlation coefficient indicated a weak but positive relationship. Conclusion: There is a statistically significant relationship between husbands' emotional support and maternal self-confidence in exclusive breastfeeding. Greater emotional support from husbands is associated with higher maternal confidence in breastfeeding. Therefore, increasing husbands' involvement through emotional support is essential to improve the success of exclusive breastfeeding.